Increasing NDC ambition and improving national low-emission strategies by linking knowledge to policy: Colombia, Kenya, and Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Colombia, Kenya, and Vietnam increased the ambition of their National Determined Contributions (NDCs) mitigation targets and improved inventories and low-emission strategies based on CCAFS, US Department of Agriculture (USDA) and partners' collaboration to better link existing knowledge products to policy. NDC improvements included improved activity data (fertilizer in Colombia), more comprehensive sector targets (livestock in Vietnam, cacao in Colombia), and inclusion of climate-smart agriculture county plans for mitigation and adaptation for implementing NDCs in Kenya.